2009
DOI: 10.1016/j.jcv.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty with mumps diagnosis: What is the contribution of mumps mimickers?

Abstract: Although there was co-circulation of other viral pathogens during the mumps outbreak, no difference was observed in the prevalence between patients who presented with or without parotitis. The low positivity rate for specimens submitted for mumps diagnostics was likely the result of increased Public Health messaging and physician inexperience in recognizing mumps infection, suggesting the clinical acumen for mumps diagnosis based solely on clinical presentation is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Among 5 such studies, the average EBV detection rate was 20% (range, 6%–25%); however, EBV test methods varied [69, 28, 29]. We detected EBV in 13% of samples; however, the lower frequency reported here might have resulted from the initial surveillance focus on influenza-associated NMP.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Among 5 such studies, the average EBV detection rate was 20% (range, 6%–25%); however, EBV test methods varied [69, 28, 29]. We detected EBV in 13% of samples; however, the lower frequency reported here might have resulted from the initial surveillance focus on influenza-associated NMP.…”
Section: Discussionmentioning
confidence: 61%
“…Acute, viral non-mumps parotitis (NMP) is an infrequently recognized illness that occurs sporadically and has been associated with multiple etiologic agents, including adenoviruses, enteroviruses (coxsackieviruses, echoviruses), Epstein-Barr virus (EBV), human herpes virus (HHV) 6A and 6B, influenza A(H3N2) and influenza B viruses, human parainfluenza viruses (HPIVs) 1–3, and parvovirus B-19 [1–9]. While there is no systematic surveillance for NMP, results of several studies have suggested EBV is the most frequently detected virus among patients with NMP, followed by HPIV3, HPIV2, and adeno-viruses [69].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mumps is a vaccine-preventable disease that is endemic in most parts of the world. [1] Mumps disease outbreak occurred in an unvaccinated population of Chikkahallivana village in Davangere district of Karnataka, India in January 2014. Most of the affected unimmunized population belonged to a worker community who opted out of scheduled vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…2) but only 4 (6%) of whom were laboratory confirmed. In 1994-1998, these age groups should have been at least partially vaccinated which renders clinical diagnosis particularly unreliable [9,10]. The number of cases in 1994-1998 may therefore be an overestimation and the current increase even more marked.…”
Section: Discussionmentioning
confidence: 99%